SEVERITY OF CORONARY ARTERY DISEASE IN OBESE PATIENTS UNDERGOING CORONARY ANGIOGRAPHY: Coronary Artery Disease in Obese Patients - Javed, Dr Asim; Sharif, Hamid; Ali, Jahanze; Kayani, Azhar Mahmood (Pakistan Armed Forces Medical Journal, 2012)
Objective: To assess the relationship of severity of coronary artery disease with obesity in patients undergoing coronary angiography.Design: Cross sectional study.Place and Duration of Study: Armed Forces Institute of Cardiology – National Institute of Heart Diseases (AFIC-NIHD), 1st February 2010 to 31st August 2010Patients and Methods: The study population included 468 patients undergoing coronary angiography. Obesity was classified according to the BMI using the National Institutes of Health (NIH) criteria as normal (BMI 21–24 kg/m2), overweight (BMI 25–29 kg/m2), obesity class I (BMI 30–34 kg/m2), obesity class II (BMI 35 to 39 kg/m2 and obesity class III (BMI 40 or above kg/m2).Coronary angiography data were obtained from the Siemens Queries software system, which maintains the database including detailed angiographic findings of all patients at this institution. Significant lesions were defined as those with >70% diameter narrowing of coronary arteries (>50% for the left main coronary artery). We attempted to quantify the “severity of CAD” by ascertaining the prevalence of High-Risk Coronary Anatomy (HRCA).Results: Insignificant difference was observed in traditional risk factors i.e. age, diabetes mellitus and smoking except hypertension and gender. Statistically significantly low prevalence of HRCA was encountered in the obese group (57.7%) as compared to normal/overweight group (75.8%) (p < 0.05).Conclusion: We conclude that obesity is associated with less severe coronary artery disease.